CHARACTER ASSOCIATION AND PATH ANALYSIS STUDIES OF YIELD AND QUALITY PARAMETERS IN BASMATI RICE (ORYZA SATIVA L.) - C. R. ALLAM,; H. K. JAISWAL,; A. QAMAR, (The Bioscan, 2014)
A study of correlation and path analysis was undertaken in 23 genotypes of basmati rice for grain yield, its componenttraits and grain quality traits. Yield per plant had highly significant positive genotypic and phenotypic correlation with days to maturity (rp =0.3998, rg =0.4190), effective panicles (rp =0.7295, rg =0.7443), spikelets per panicle (rp =0.4892, rg =0.5069) and amylose content (rp=0.4155, rg =0.4490). Kernel L/B ratio showed positive and significant correlation with KLAC (rp=0.5510, rg =0.5790) and showed negative and significant correlation with elongation ratio (rp=-0.4235, rg =-0.4397). Correlation studies indicated that close relationshipbetween genotypic and phenotypic correlation coefficients and magnitude of genotypic correlation were higherthan their corresponding phenotypic correlation for most of the characters. Path coefficient analysis revealed that the number of characters chosen for the study were very much appropriate as evident from low value of residual effect (0.1614).Effective panicles per plant imparted the highest positive direct effects (0.6169) on yield followed by test weight (0.5545), spikelets per panicle (0.5268), kernel length (0.3364) and spikelet fertility (0.2175). The study suggested that days to maturity, effective panicles, spikelets per panicle, spikelet fertility, test weight, kernel length, kernel L/B ratio, KLAC, elongation ratio are important traits which should be used asselection criteria to develop high yielding and better quality varieties in basmati rice.